PURE WATER IS THE FUNDAMENTAL RIGHT OF ALL - John Kennedy, S. M. (Journal of Dharma, 2006)
In 1995, the then World Bank Vice President, Ismail Serageldin said: “If the wars of this century were fought over oil, the wars of the next century will be fought over water.” It is deeply disturbing to realise that with each passing day our deepest worry is the future of the planet’s fresh water supply. “Fierce national competition over water resources has prompted fears that water issues contain the seeds of violent conflict,” Kofi Anna, Secretary General of the United Nations said in a message for World Water Day (March 22, 2002). “But the water problems facing our world need not be only a cause of tension; they can also be a catalyst for co-operation,” he added.